Excimer retreatment for scarring and regression after photorefractive keratectomy for myopia. Issue 8 (August 1995) - Sutton, G; Kalski, R S; Lawless, M A; Rogers, C
Abstract : AIMS/BACKGROUND--Scarring associated with regression of refractive effect can occur after photorefractive keratectomy (PRK) for myopia. The experience of treating these complications is reported. METHODS--Eighteen of 285 eyes (6.3%) were retreated with the excimer laser. Age, sex, preoperative primary treatment keratometry, pre-primary treatment, pre-retreatment and post-retreatment spherical equivalents, best corrected and uncorrected visual acuities were recorded and analysed. RESULTS--At 6 months post-retreatment, the mean spherical equivalent was -2.07 dioptres (D) (SD 4.60 D). This spherical equivalent persisted in eyes followed for 12 months (-2.85D, SD 4.09 D). Nine of 18 eyes (50%) had uncorrected visual acuity of 6/12 (20/40) or better. If retreatment was undertaken within 6.5 months of the initial PRK, then scarring was likely to recur (p = 0.035). Nine of 10 eyes (90%) which had a retreatment spherical equivalent less than two thirds of their primary treatment spherical equivalent were within plus or minus 1.25D from emmetropia after retreatment. Four of 11 eyes (36%) followed for 12 months after retreatment rescarred with further regression. CONCLUSION--The data showed that eyes with scarring and regression of myopia should not be treated with PRK within 6 months of the initial procedure. Eyes with the highest percentage of regression towards their initial myopia tend to have a poor response to retreatment.